The deer cry pavilion : - Barr, Pat (Macmillan, 1968)
This is a sequel to "The Coming of the Barbarians" and deals with the period from the accession of Emperor Meiji to the end of the Ruso-Japanese war. In the author's own words, it is "a story of Meiji Japan through the eyes of the Westerners who were involved in the process of its rapid modernization." The Japanese reactions to this process are recorded and explained.